Convective heat transfer - Kakaç, S. (Sadık); Yener, Yaman, 1946-; Pramuanjaroenkij, A. (Anchasa) (CRC Press, 2014)
"With clear, concise coverage of the basics of convection, this textbook is written for senior/graduate students, from mechanical and other engineering majors, who have taken a basic heat transfer course. Balancing basic concepts with engineering applications, the new edition is ideal for those wanting to learn more heat transfer for research work and advanced coursework. Convective heat transfer is important for many areas, including biomedical applications and energy technologies. This third edition features a complete new chapter on microscale and nanoscale convective heat transfer, and more coverage of numerical/computer methods"--